Underwater gliders control strategies: A review - Ullah, B. (Institute of Electrical and Electronics Engineers Inc., 2015)
Underwater Gliders (UGs) are a type of Autonomous Underwater Vehicle (AUV) that uses buoyancy engines, an energy efficient locomotion, primarily for oceanography. In this paper, control strategies for existing underwater gliders are reviewed. A total of 50 papers indexed by Scopus with keywords control and underwater gliders were reviewed from 1989 to 2014. The majority of gliders use classical controllers, which cannot dynamically compensate for un-modeled hydrodynamic forces and unknown variations in water current and wind. With increasing operational depths and larger payloads, control strategies will become an increasingly important aspect for these gliders. Control strategies implemented in underwater gliders were reviewed and alternative control strategies are proposed. Â© 2015 IEEE.